Analisis Struktur Tema-Rema dalam Berita Kompas.com - Ananti, Mutia; Usman, Usman; Baharman, Baharman (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study examines the structure and pattern of theme-rheme in Kompas.com news. This study aims to describe the structure and dominant pattern of theme-rheme in Kompas.com news texts. This study uses the Systemic Functional Linguistics (LSF) approach developed by Halliday. The research method used is descriptive qualitative with data collection techniques in the form of documentation, reading, and recording. Data were taken from 32 online news published in the national rubric in Kompas.com during December 2024. The results of the study indicate that the interpersonal theme shows an emphasis on the relationship between the writer and the reader in presenting information. Followed by the textual theme. In terms of patterns, it was found that the sequential theme-rheme pattern appeared most often, followed by causal and argumentative patterns. This study shows that the strategy for compiling themes-rhemes in online news reflects a communicative and effective pattern of information delivery.